Intervention Effectiveness Research: Quality Improvement and Program Evaluation - Monsen, Karen A. (Springer International Publishing, 2018)
Do interventions improve health outcomes? This volume provides a model and road map to answer clinical questions related to intervention effectiveness research, quality improvement, and program evaluations. It offers clear and simple guidance for all phases of a clinical inquiry projects from planning through dissemination and communication of results and findings. The book emphasizes the value and importance of leveraging existing data to advance research, practice, and quality improvement efforts. Intervention and Effectiveness Research is a practical guide for organizing and navigating the intersections of research and practice. Structure, process and outcome worksheets for every step are provided together with examples from diverse settings and populations to lead readers through the process of implementing their own projects. The author guides readers through the process of designing, implementing, and evaluating project s. This book is intended for teachers of DNP and PhD programs in nursing and other disciplines, their students, and healthcare leaders who need to leverage data to demonstrate care quality and outcomes.